Moderating Effects of Friendship and Family Support on the Association Between Bullying Victimization and Perpetration in Adolescents - Ho, Hsing-Ying (Journal of interpersonal violence, 2022)
School bullying can cause severe mental health problems for both victims and perpetrators. However, the association between bullying victimization and perpetration has rarely been discussed, and no study has investigated the effects of social support, such as friendship and family support, in moderating this association. Therefore, the authors examined the moderating effects of friendship and family support on the association between bullying victimization and perpetration in adolescents. Data were obtained from the 2009 Project for the Health of Adolescents. Through multistage stratified cluster sampling, 13 junior and 10 senior high schools in southern Taiwan were selected, resulting in a representative sample of 6,445 students from grades 7 to 12. School bullying and family support were examined using the Chinese version of the School Bullying Experience Questionnaire and the Family adaptability, partnership, growth, affection, resolve instrument, respectively. Friendship support was measured using the subscale of the Taiwanese Quality of Life Questionnaire for Adolescents and adolescents? number of friends, time spent with friends, and friend distributions. Linear regression modeling and the Johnson?Neyman technique were used to examine the moderating effects of friendship and family support on the association between bullying victimization and perpetration. For active bullying, having fun and talkative friends and friends outside school negatively moderated the intensity of the association between bullying victimization and perpetration (regression coefficients: ?0.02 to ?0.05), whereas, for passive bullying, only friends outside school negatively moderated the intensity of the association (regression coefficient: ?0.05). By contrast, some components of friendship support positively moderated the associations. These findings suggest that higher friendship quality and having more friends outside of school attenuate the association between bullying victimization and perpetration in adolescents, thus increasing the understanding of the moderating role that social support play in such associations.